Can tests improve learning in real university classrooms?. Issue 8 (17th November 2021) - Lamotte, Mathilde; Izaute, Marie; Darnon, Céline
ABSTRACT: Long-term memory of a stimulus is likely to be better when individuals are tested on the stimulus than when they merely restudy it. This "testing effect" suggests tests could be used in real classroom contexts to improve students' academic performance. However, real classroom contexts can be regarded as evaluative contexts which might change the meaning and effects of tests. The present paper reviews existing evidence of the positive effect of testing on learning in real classroom academic settings and on learning material that is part of the curriculum. While underscoring the positive effects testing can have in real classroom contexts, it also highlights features of classroom testing that may be particularly helpful for teachers. The review also points to important challenges that will need to be addressed in future research into the testing effect in real classroom contexts.